KOGNITIF MUHAMMAD DI MASA PRA KENABIAN DALAM FRAME JEAN PIAGET - Fitri Aulia (TASÂMUH, 2016)
This research tries to explore cognitive development of Prophet Muhammad in teenage period from Jean Piaget’s framework. This library research explains historical record of Prophet Muhammad before prophethood. Jean Piaget highlights individual development in four phases, i.e. sensory motoric, pre-operational, concrete operational and formal operational. Prophet Muhammad before achieving revelation period had experienced some development phases relating to Jean Piaget’s category. They are seen through some ability, i.e. 1) ability to use archery in early teenage period, 2) strong memory, 3) ability to process information properly, 4) problem solving ability, 5) ability to plan the future, 6) ability to learn, notice, observe, imagine, predict, assess, and think on his surroundings.